Adding weekly irinotecan to high-dose 5-fluorouracil and folinic acid (HD-5-FU/FA) after failure for first-line HD-5-FU/FA in advanced colorectal cancer - a phase II study - Hofheinz, Ralf-Dieter; Hartung, Gernot; Samel, Stefan; Emig, Michael; Pilz, Lothar R.; Willeke, Frank; Hochhaus, Andreas; Hehlmann, Rüdiger; Queißer, Wolfgang (Anti-cancer drugs, 2002)
Irinotecan (CPT-11) has been shown to prolong survival and improve quality of life in comparison to best supportive care in colorectal cancer patients with pretreatment of bolus 5-fluorouracil (5-FU). After first-line 24-h high-dose (HD) 5-FU/folinic acid (FA) an objective response rate of 11% with 3-weekly CPT-11 350 mg/m2 was reported. In the present study we investigated weekly CPT-11 in combination with 24-h HD-5-FU/FA as second-line treatment after prior exposure to 24-h HD-5-FU. Synergy between 5-FU and CPT-11 is the rationale to combine both substances for second-line therapy in order to overcome resistance to 5-FU. Thirty-five patients were recruited in a single institution to receive 6 × weekly CPT-11 80 mg/m2, FA 200 mg/m2 and 24-h HD-5-FU 2000 mg/m2. Treatment was repeated on day 57. Patient characteristics: M/F=20/15, median WHO performance status 1, range (0-2). Thirty-four patients were evaluable for response: partial response 17% and no change 40%. Median time to progression and overall survival were 3.3 and 8.4 months, respectively. All patients were evaluable for toxicity analysis (National Cancer Institute Common Toxicity Criteria grade 3): leukocytopenia 3%, diarrhea 12% and vomiting/nausea 6%. Of the assigned doses, a median 100% of 5-FU and 92% of CPT-11 were administered during the first cycle of chemotherapy. We conclude that weekly CPT-11 and HD-5-FU/FA is an active and safe combination chemotherapy resulting in response rates in the upper range of other CPT-11-based second-line regimen. The toxicity profile in our series compared to 3-weekly CPT-11 seems favorable.